Extracellular matrix in ocular homeostasis and diseases: The heroes, the villains, and the magic - Aldrovani, Marcela [UNESP]; Cristovam, Priscila Cardoso; Pascoli, Ana Lúcia [UNESP]; da Silva, Germana Alegro [UNESP]; Madruga, Gabriela Morais [UNESP]; Bandeira e Silva, Francisco; Laus, José Luiz [UNESP] (My University, 2018)
The eyes are highly diversified photosensitive structures. In all vertebrates, eyes resemble in molecular composition and are predominantly composed of extracellular matrix (ECM). Compared with other structures, the eyes have ECM in unique arrangements. Because the ocular ECM is labile and dynamic, when remodeling, it may lead to a series of diseases or alterations that impair vision. Post-translational processing of ECM molecules of the eye can be impaired by multiple multifactorial conditions that trigger the onset of ocular diseases, including corneal dystrophies, glaucoma, macular degeneration, and tumors. Besides, the ECM is the link that connects the eyes to other structures of the body, so a variety of systemic hereditary or autoimmune connective tissue disorders can affect the ocular homeostasis. This work explores the dual role (from hero to a villain) of ECM in ocular homeostasis and diseases and discusses how this duality can be magically used to treat ocular diseases. The view on ECM biology offered by this work is translational and address concepts of basic science and clinicalsurgical issues.
Keywords: Eye; Matrix remodeling; Ophthalmic disorders; Regenerative medicine